The Effect of Debt Policy, Sales Growth, and Good Corporate Governance on Firm Value in Consumer Non-Cyclicals Companies Listed on the Indonesia Stock Exchange for the 2021–2023 Period - Zahira Puteri Aisyah; Susi Indriani; Sri Zulaihati (Research Trend in Technology and Management, 2025)
In this research, we examine non-cyclical consumer companies listed on the Indonesia Stock Exchange (IDX) in the period 2021 to 2023 to observe the effect of debt policy, sales growth, and good corporate governance on company value. Good corporate governance is measured by the percentage of independent commissioners, sales growth, and debt policy as measured by the debt to equity ratio (DER) as independent variables. The dependent variable is the company value represented by the price to book value ratio (PBV). The method used is quantitative. Data were obtained from 76 companies selected based on certain criteria. The analysis was carried out using EViews software version 12 with multiple linear regression of panel data. The results of the study show that debt policy has a positive effect on the value of non-cyclical consumer companies. In addition, increased sales also significantly increase company value. However, good corporate governance does not have a significant impact on company value. Simultaneously, the value of non-cyclical consumer companies on the IDX in 2021 to 2023 is influenced by debt policy, sales growth, and good corporate governance.